Perbedaan Kepuasan Ibu Menyusui dengan Pemberian Metode SPEOS (Stimulasi Pijat Endorphin, Oksitosin dan Sugestif) di Wilayah Kerja Puskesmas Tejakula I Tahun 2022 - Luh Astini Dewi; Ni Wayan Armini; Ni Gusti Kompiang Sriasih (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
The success of exclusive breastfeeding is determined in early breastfeeding. Many mothers feel dissatisfied in breastfeeding because the breastmilk is no initial or non fluent. The purpose of this research is to  determine the difference of maternal breastfeeding satisfaction before and after giving the SPEOS method. The research method  is quasi-experimental and use two groups pretest posttest design. The sample is 18 mothers in intervention group and 18 mothers in control group by using purpossive sampling. Measurement of maternal breastfeeding satisfaction  use the MBFES tool. The data distribution  is normal and the data analysis use  Dependent T-Test and Independent T-Test with α=0,05. The result of this research is there is defference maternal breastfeeding  satisfaction  before  and after  giving  the  SPEOS method   (p value0,001), there is difference before and after giving convensional care  (p value=0,012), there is no difference  maternal breastfeeding satisfaction before treatment in intervention and control group (p value=0,156), there is difference maternal breastfeeding satisfaction before treatment  in intervention and control group (p value0,001). Giving SPEOS method make mothers feel confident and relax and can increase the breastmilk production. It is suggested giving SPEOS method to the early breastfeeding mother  for increasing  the maternal breastfeeding satisfaction.